Implementation of SQ3R to Increase Reading Interest, Critical Thinking Skills, and Ability to Understand Indonesian Language Reading of 6th Grade Indonesia A Students (International Journal of Theory and Application in Elementary and Secondary School Education, 2019)
The purposes of this research was to analyzing the development of reading interest, critical thinking skills and reading comprehension skills by applying SQ3R (Survey, Question, Read, Recite and Review). This research method is Classroom Action Research, data collection was done through observation, written tests, interviews and field notes which were analyzed descriptive qualitative. There was an increase in student's interest in reading in Cycle I by 50% to 100% in Cycle II and III. In students' critical thinking skills, namely from 87.5% in Cycle I to 100% in Cycle II and III. Student reading comprehension ability also show improvement, in Cycle I was 67.4; Cycle II was 84.2 and Cycle III was 88.6. From student interviews and questionnaires showed that students agreed through the application of SQ3R to increase students' reading interest, critical thinking skills and reading comprehension skills.